Penerapan Problem Based Learning untuk Meningkatkan Hasil Belajar Matematika Kelas VIII.2 SMPN 13 Pekanbaru - Bokhari, Khairiati; Kartini, Kartini; Anggraini, Rini Dian (Polinomial : Jurnal Pendidikan Matematika, 2025)
This research was motivated by the fact that the mathematics learning outcomes in class VIII.2 of SMPN 13 Pekanbaru were low, with only 39.53% of students reaching the Learning Objectives Achievement Criteria. This study aimed to improve students' mathematics learning outcomes by implementing the Problem Based Learning (PBL) model. This research is a collaborative Classroom Action Research (CAR) conducted in two cycles. The subjects of this study were all 43 students of class VIII.2, who were sampled using a census technique. The research instruments used were learning outcome tests and observation sheets. Data were analyzed quantitatively for the test results and qualitatively for the observation sheets. The research findings showed an increase in the percentage of students who reached the Learning Objectives Achievement Criteria from a baseline score of 39.53%, which rose to 48.83% in Cycle I and 65.11% in Cycle II. Therefore, it can be concluded that the implementation of the PBL model is effective in improving students' mathematics learning outcomes.